Abstract Volterra Equations with State-Dependent Delay - Lizama-Yanez, C (Rocky Mountain Mathematics Consortium, 2015)
By using the theory of resolvent families, fixed point theorems and measures of noncompactness, we prove the existence of mild solutions on a compact interval for a semilinear Volterra equation with state-dependent delay. An example is given. © 2015 Rocky Mountain Mathematics Consortium.